Kajian Sistem Pelaporan Farmakovigilans Berdasarkan Pelaporan Rumah Sakit Di Sumatera Utara Pada Rentang 2019-2024 - Mai Syaroh Nasution; Wiryanto Wiryanto; Grace Wangge (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Pharmacovigilance safeguards patient safety, yet hospital ADR reporting in North Sumatra remains limited. This research to assess compliance with BPOM’s 10 completeness criteria and identify determinants that support or hinder implementation. Methods: A mixed methods approach with a sequential explanatory design was applied. descriptive analysis of 2019-2024 e-MESO reports and in-depth interviews with hospitals categorized as Complete, Incomplete, and Non-reporting. Results: Out of 210 hospitals, only 11 (5%) actively reported through e-MESO, producing 50 reports, 98% complete and 2% incomplete. About 74% were spontaneous reports, mostly skin reactions, with 40% serious cases in elderly patients. Qualitative analysis revealed seven main themes: understanding, reporting process, barriers, management support, e-MESO system, expectations, and interprofessional collaboration. Conclusion: While individual report completeness is high, system-level participation is low, so full compliance with the 10 criteria is not yet achieved. Reporting quality is largely shaped by managerial support, organizational readiness, and interprofessional collaboration. Recommended actions include expanding SOP-based reporting on the 10 criteria, appointing a clinical pharmacist as the person-in-charge, conducting cross-profession training, and coordinating e-MESO technical issues with BPOM particularly strengthening type-C hospitals.